Kinematic analysis of the snatch lift with elite female weightlifters during the 2010 World Weightlifting Championship - Akkus, A. (The Journal of Strength and Conditioning Research, 2012)
The objectives of this study were to determine the mechanical work, the power output, and the angular kinematics of the lower limb and the linear kinematics of the barbell during the first and second pulls in the snatch lift event of the 2010 Women's World Weightlifting Championship, an Olympic qualifying competition, and to compare the snatch performances of the women weightlifters to those reported in the literature. The heaviest successful snatch lifts of 7 female weightlifters who won gold medals were analyzed. The snatch lifts were recorded using 2 Super-Video Home System cameras (50 fields·s-1), and points on the body and the barbell were manually digitized using the Ariel Performance Analysis System. The results revealed that the duration of the first pull was significantly greater than the duration of the transition phase, the second pull, and the turnover under the barbell (p < 0.05). The maximum extension velocities of the lower limb in the second pull were significantly greater than the maximum extension velocities in the first pull. The fastest extensions were observed at the knee joint during the first pull and at the hip joint during the second pull (p < 0.05). The barbell trajectories for the heaviest snatch lifts of these elite female weightlifters were similar to those of men. The maximum vertical velocity of the barbell was greater during the second pull than in the first pull (p < 0.05). The mechanical work performed in the first pull was greater than the second pull, and the power output during the second pull was greater than that of the first pull (p < 0.05). Although the magnitudes of the barbell's linear kinematics, the angular kinematics of the lower limb, and other energy characteristics did not exactly reflect those reported in the literature, the snatch lift patterns of the elite women weightlifters were similar to those of male weightlifters.